A comprehensive review on the recycling of spent lithium-ion batteries: Urgent status and technology advances. (15th March 2022) - Jin, Shan; Mu, Deying; Lu, Ziang; Li, Ruhong; Liu, Zhu; Wang, Yue; Tian, Shuang; Dai, Changsong
Abstract: The burgeoning development of lithium-ion battery technology is imperative, not only realizing targets for reducing greenhouse gas emissions, but also changing the way of global communication and transportation. As the demand increases, the quantity of discarded lithium-ion batteries (LIBs) has been continuously rising, bringing a tough waste-management challenge for recycling service sectors at end-of-life. Nevertheless, spent LIBs also bring an opportunity because of their double-edged competitive advantages in ecology and economy. This comprehensive review is initiated on the background of the skyrocketing global lithium ion battery market, covering the possible environmental hazard and huge economic potential, with emphasis placed on state-of-the-art reclamation technologies. During the past decade, significant technological advances have been made in treatment processes of spent LIBs, such as battery stabilization, electrolyte collection, electrode separation, active material leaching and purifying. Besides, effective reclamation strategies, based on pyrometallurgy, hydrometallurgy or both, are in full swing to maximize resource recovery. Here, we provide a systematic overview of spent LIB recycling technologies from an all-sided perspective in current status. Perspectives for developing technologies, establishing evaluation standards, and exploring correlative scientific issues are discussed. A closed-loop recycling chain entailing utilization, reclamation and resynthesis is recommended for the future outlook of spent LIB recycling. Graphical abstract: A closed-loop chain entailing echelon utilization, reclamation and resynthesis is systematically summarized as the future tendency of spent LIB recycling. Image 1 Highlights: Explaining the urgent status of battery recycling from market potential to economic and environmental impacts. Summarizing widespread pretreatment technology, including stabilization, electrolyte collection and electrode separation. Elaborating effective reclamation strategies, based on pyrometallurgy, hydrometallurgy or both. Recommending a closed-loop recycling chain for the future outlook of spent LIBs recycling.